Evaluating suitability of glutaraldehyde tanning in conformity with physical properties of conventional chrome-tanned leather - Uddin, Md. Minhaz (Array, 2020)
Leather manufacturing involves a number of unit processes, out of which tanning is the most important in so far as it converts the putrescible hides/skins into non-putrescible leather. In this study, glutaraldehyde has been exploited as a means to reduce the use of basic chromium sulfate for the production of quality shoe upper crust leather. The paper consists in studying the physical properties of aldehyde-tanned leather and chrome-tanned leather. The aim is to find out the possibility of replacing the wet-blue leather, containing Cr(III) salts, with the glutaraldehyde-tanned wet-white leather. The physical properties of the aldehyde-tanned leather were evaluated, analyzed and compared with the conventional chrome-tanned shoe upper crust leather. Statistical analysis illustrated that the tensile strength, the percentage of elongation, stitch tear strength, Baumann tear strength and grain crack strength of the leather was 211±1 kg/cm2, 38±0.5 %, 89±0.11 kg/cm, 63±0.4 kg/cm and 23±0.4 kg respectively. It was observed that the property of the experimental leather was quite comparable with the conventional chrome-tanned leather and able to meet the requirements of the shoe upper crust leather after re-tanning. The shrinkage temperature of the experimental tanned leather was found to be 87 °C,lower than that of corresponding control, which indicates lesser tanning power of aldehyde. However, the morphology of the aldehyde-tanned leather was quite akin with the conventional leather. This study suggests that using glutaraldehyde in the tanning process in order to minimize the chromium load in the tanning and the re-tanning process during the production of shoe upper crust leather reduces the generation of toxic waste and its impact on the environment.